2013
DOI: 10.1148/radiol.12120195
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Optimization of Chest CT Angiography with Reduced Iodine Load: Experience in 80 Patients Evaluated with Dual-Source, Dual-Energy CT

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12120195/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(65 citation statements)
references
References 27 publications
4
56
1
2
Order By: Relevance
“…Spectral imaging was recently introduced into clinical DECT imaging. Studies indicate that DECT has the potential to improve lesion detection [1,10], enhance image quality [11], reduce hardening artifacts [12] and substitute non-contrast images with virtual non-contrast [9]. Iodine map, virtual unenhanced and monochromatic images can improve lesion characterization and affect evaluation of the response to therapy and detection of oncology-related disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…Spectral imaging was recently introduced into clinical DECT imaging. Studies indicate that DECT has the potential to improve lesion detection [1,10], enhance image quality [11], reduce hardening artifacts [12] and substitute non-contrast images with virtual non-contrast [9]. Iodine map, virtual unenhanced and monochromatic images can improve lesion characterization and affect evaluation of the response to therapy and detection of oncology-related disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…9) [75]. Using dualenergy CT, iodine load can be reduced when virtual monochromatic imaging extrapolated to photon energies of 50 or 70 keV is used [83][84][85]. Saade et al reported that appropriate contrast material volume can be acquired with use of a patientspecific approach; however, this approach is complex in the clinical setting, because it requires the calculation of contrast material volume according to the equation [86].…”
Section: Reduced Contrast Medium Volumementioning
confidence: 99%
“…2). This can be effectively used to optimize iodine contrast while maintaining an acceptable signal-to-noise and contrast-tonoise ratio [46,47]. This application may be beneficial in settings in which pulmonary vascular attenuation is suboptimal because of low-contrast enhancement, intravascular embolus burden, or partial volume effects.…”
Section: Indirect Lung Perfusion Ctpa Using Dual-energymentioning
confidence: 99%